2000
DOI: 10.2166/wst.2000.0416
|View full text |Cite
|
Sign up to set email alerts
|

pH effect on the surface and bulk characteristics of metallic cations/SiO2 suspensions

Abstract: The surface and bulk properties of Al(III)/SiO2 and Fe(III)/SiO2 suspensions were determined as a function of prepared pH. The TEM results showed that Al(III) tends to form Al(OH)3 coatings on the surface of SiO2 while Fe(III) tends to form the discrete Fe(OH)2 phase in bulk solution with system pH increase. The charge reversals (CR) observed in the Al(III)/SiO2 system represent, in order of increasing pH, the point-of-zero charge (PZC) on the SiO2 substrate (CR1), the pH of surface nucleation of Al(OH)3 (CR2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…At high pH, however, the zeta potential is low inside the colloid instability region, implying that aggregation is possible. The isoelectric points of both the aluminum oxide colloid (Aerodisp W630) and the aluminum-coated silica colloid (Ludox CL) correspond well with literature data [19,27,28]. Comparing Fig.…”
Section: Characterization Of the Colloidssupporting
confidence: 86%
“…At high pH, however, the zeta potential is low inside the colloid instability region, implying that aggregation is possible. The isoelectric points of both the aluminum oxide colloid (Aerodisp W630) and the aluminum-coated silica colloid (Ludox CL) correspond well with literature data [19,27,28]. Comparing Fig.…”
Section: Characterization Of the Colloidssupporting
confidence: 86%
“…All experiments were performed at 25 • C, after adjustment to the desired pH using KOH and HNO 3 solutions, with shaking at 200 rpm. Since preliminary kinetic experiments suggested that pseudo-equilibrium was reached within 24 h, 24 h was selected as the reaction time for the equilibrium experiments [34].…”
Section: Batch Experimentsmentioning
confidence: 99%
“…In the authors' earlier study, the EM of pure SiO 2 suspensions over a range of pH values and in three different salt solutions (0, 0.1, 0.5 M) lie on a curve and the isoelectric point (IEP) is 2.00 for an SiO 2 particle [34]. Therefore, 0.1 M KNO 3 was adopted as the background electrolyte in all experiments.…”
Section: Evidences From Electrophoretic Mobility (Em) Measurementsmentioning
confidence: 99%
“…8 In literature, charge inversion is either attributed to the adsorption of unhydrolyzed ions, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] hydrolyzed ions [25][26][27][28][29][30][31][32][33] or hydroxides. [34][35][36] Which of these species is eventually responsible, remains unclear because the commonly used electrophoretic measurements (e.g. z-potential measurements) alone cannot distinguish between these three species.…”
Section: Introductionmentioning
confidence: 99%